Giant hepatic adenoma with bone marrow metaplasia not associated with oral contraceptive intake - Pilozzi Emanuela; Rossi Simone; Pezzoli Francesca; D'Angelo Francesco; Aurello Paolo; Nigri Giuseppe R; Ramacciato Giovanni; Ercolani Giorgio; Ravaioli Matteo (World Journal of Surgical Oncology, 2006)
Abstract Background Hepatocellular adenomas are the most common benign liver tumors. They are usually related to oral contraceptive intake. Case presentation This case describes a 58-year-old woman admitted to our institution for a hepatic mass incidentally discovered during a routine examination. The patient, who was never on oral contraceptives, was asymptomatic upon admission. She underwent a thorough diagnostic evaluation and then a hepatic right trisegmentectomy. The histologic evaluation of the mass showed that it was a hepatocellular adenoma with areas of bone marrow metaplasia. Conclusion Bone marrow metaplasia has rarely been found associated to liver tumors. The presence of marrow-derived hepatic progenitor cells might be the source of both adenoma hepatocytes and bone marrow differentiated cells. To our knowledge, this is only the second case in the English literature in which areas of bone marrow metaplasia were found in a hepatocellular adenoma.